The Relationship between self-coping and depression in older adults with hypertension - Nugroho, Rafli Bagas; Sudyasih, Tiwi; Suratini, Suratini (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Depression is a common mental health problem among the elderly and significantly affects their quality of life and psychological well-being. This condition is often underdiagnosed because its symptoms are frequently considered part of the normal aging process. Chronic diseases such as hypertension can worsen psychological conditions due to physical limitations and prolonged psychosocial stress. Coping mechanisms play an important role in preventing and managing depression, while inadequate coping may increase vulnerability to depression among elderly individuals with hypertension. Purpose: To analyze the relationship between self-coping and depression among older adults with hypertension. Method: This study used a descriptive correlational design with a cross-sectional approach. The study sample consisted of 44 elderly people with hypertension in Glagah Hamlet, Nglegi Village, Patuk District, Gunungkidul Regency, selected using a purposive sampling technique. Data collection was conducted using a self-coping questionnaire and the Patient Health Questionnaire-9 (PHQ-9). Data analysis was performed using the Kendall's Tau correlation test with a significance level of p < 0.05. Results: T The results showed that most respondents had high coping mechanisms (84.1%), and the majority were categorized as not depressed (61.4%). The Kendall’s Tau test revealed a correlation coefficient of −0.431 with a p-value of 0.003, indicating a significant negative relationship with a moderate correlation strength between coping mechanisms and depression levels. Conclusion: There is a significant negative relationship between coping mechanisms and depression levels among elderly patients with hypertension. Higher coping ability is associated with lower levels of depression. Strengthening adaptive coping strategies is important to maintain mental health among elderly individuals with chronic diseases. Keywords: Depression; Hypertension Older Adults; Self-Coping. Pendahuluan: Depresi merupakan masalah kesehatan mental yang sering dialami oleh lansia dan berdampak pada kualitas hidup serta kesejahteraan psikologis. Kondisi ini kerap tidak terdeteksi karena gejalanya dianggap sebagai bagian dari proses penuaan. Penyakit kronis seperti hipertensi dapat memperburuk kondisi psikologis akibat keterbatasan aktivitas fisik dan tekanan psikososial yang berkepanjangan. Koping diri berperan penting dalam mencegah dan mengendalikan depresi, sementara koping yang tidak adekuat dapat meningkatkan kerentanan depresi pada lansia dengan hipertensi. Tujuan: Untuk menganalisis hubungan antara koping diri dengan tingkat depresi pada lansia penderita hipertensi. Metode: Penelitian ini menggunakan desain deskriptif korelasional dengan pendekatan cross-sectional. Sampel penelitian berjumlah 44 lansia penderita hipertensi di Dusun Glagah, Desa Nglegi, Kecamatan Patuk, Kabupaten Gunungkidul, yang dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan menggunakan kuesioner koping diri dan Patient Health Questionnaire-9 (PHQ-9). Analisis data dilakukan menggunakan uji korelasi Kendall’s Tau dengan tingkat signifikansi p < 0.05. Hasil: Sebagian besar responden memiliki koping diri pada kategori tinggi (84.1%) dan mayoritas responden berada pada kategori tidak depresi (61.4%). Hasil uji Kendall’s Tau menunjukkan nilai koefisien korelasi sebesar −0.431 dengan nilai p = 0.003, yang menandakan adanya hubungan negatif yang signifikan dengan kekuatan korelasi sedang antara koping diri dan tingkat depresi. Simpulan: Terdapat hubungan negatif yang signifikan antara koping diri dan tingkat depresi pada lansia penderita hipertensi. Semakin tinggi kemampuan koping diri yang dimiliki lansia, maka semakin rendah tingkat depresi yang dialami. Penguatan koping diri adaptif penting dilakukan sebagai upaya menjaga kesehatan mental lansia dengan penyakit kronis. Kata Kunci: Depression; Hypertension Older Adults; Self-Coping.